2016
DOI: 10.1021/acsami.6b11766
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Luminescence Quenching of K2Bi(PO4)(MoO4):Eu3+ Phosphors with Efficiencies Close to Unity

Abstract: A very good light emitting diode (LED) phosphor must have strong absorption, high quantum efficiency, high color purity, and high quenching temperature. Our synthesized KBi(PO)(MoO):Eu phosphors possess all of the mentioned properties. The excitation of these phosphors with the near-UV or blue radiation results in a bright red luminescence dominated by the D → F transition at ∼615 nm. Color coordinates are very stable when changing Eu concentration or temperature in the range of 77-500 K. Furthermore, samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 54 publications
3
36
0
1
Order By: Relevance
“….655 and 1.733 ms, respectively. The above results indicated that the PL lifetime values reasonably increased with increasing Eu 3+ concentration in the structure, which can be attributed to energy migration between Eu 3+ ions [57][58][59][60][61][62]. The uorescence lifetime of Ba 2 Lu 4.98Àx Eu x La 0.02 B 5 O 17 (x ¼ 0.1, 0.3, 0.5, 0.6, 0.7, 0.9 and 1.0) phosphor is short enough for potential application in near-UV excited WLEDs applications.…”
mentioning
confidence: 99%
“….655 and 1.733 ms, respectively. The above results indicated that the PL lifetime values reasonably increased with increasing Eu 3+ concentration in the structure, which can be attributed to energy migration between Eu 3+ ions [57][58][59][60][61][62]. The uorescence lifetime of Ba 2 Lu 4.98Àx Eu x La 0.02 B 5 O 17 (x ¼ 0.1, 0.3, 0.5, 0.6, 0.7, 0.9 and 1.0) phosphor is short enough for potential application in near-UV excited WLEDs applications.…”
mentioning
confidence: 99%
“…The broad excitation band in the PLE spectrum ranging from 280 to 400 nm with a maximum value at 325 nm is due to the 4f 7 –4f 6 5d 1 transition of the Eu 2+ ion, illustrating that the phosphor can be efficiently pumped by n‐UV light . Due to the electronic transition of the Eu 2+ ion from the 5d excited state to the 4f state, the PL spectra show an asymmetric emission band peaking at 530 nm …”
Section: Resultsmentioning
confidence: 96%
“…The results are presented in Figure . Each decay curve can be fitted with a second‐order exponential function based on the following equation: Ifalse(tfalse)=A1expfalse(tfalse/τ1false)+A2expfalse(tfalse/τ2false),…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the Eu 3+ ion, as an obbligato member of RE ions, is most frequently used as a red-emitting activator since its narrow red emission originating from 5 D 0  →  7 F 2 transition 23,24 . Up to date, some Eu 3+ -activated red-emitting phosphors, such as Li 3 Ba 2 Y 3 (WO 4 ) 8 :Eu 3+ , Ca 2 Ga 2 SiO 7 :Eu 3+ and Y 2 Mo 4 O 15 :Eu 3+ , were successfully synthesized 2527 .…”
Section: Introductionmentioning
confidence: 99%